2022
DOI: 10.1111/1756-185x.14520
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with social participation and community ambulation in people with osteoarthritis: Findings from the Canadian Longitudinal Study on Aging

Abstract: Aim: Walking in the community allows participation in meaningful activities which positively influences self-rated health and quality of life. Our objective was to identify factors associated with social participation and community ambulation in a representative sample of Canadian adults with osteoarthritis (OA). Methods: Data were from >3800 participants in the Baseline Tracking Dataset of the Canadian Longitudinal Study on Aging with OA of the hip and/or knee. Outcomes included frequency of participation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Compared to men, women with OA report greater difficulty with activities such as climbing up and down stairs and walking 500 m without walking aids [ 70 ], and as age increases, women with arthritis report higher walking limitations than men [ 16 ]. Additionally, using the Tracking cohort of the CLSA (distinct from the cohort in the current study), it was also found that Canadian adults with OA of the lower extremity, aged 45 and over, were less likely to walk outside their home and yard if they were female [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to men, women with OA report greater difficulty with activities such as climbing up and down stairs and walking 500 m without walking aids [ 70 ], and as age increases, women with arthritis report higher walking limitations than men [ 16 ]. Additionally, using the Tracking cohort of the CLSA (distinct from the cohort in the current study), it was also found that Canadian adults with OA of the lower extremity, aged 45 and over, were less likely to walk outside their home and yard if they were female [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with OA, various factors to date have also been associated with community ambulation, such as: neighbourhood safety [ 23 ], knee pain severity, comorbidities, degree of walking limitation, perceived need for walking aids and assistance, and access to a car/public transportation [ 13 ]. Canadian adults age 45 and over with OA of the lower extremity are less likely to walk in the community if they have lower endurance, lower self-rated health, severe pain, and are female; and more likely to walk outside if they have fewer chronic health conditions, the weather is warmer, and if they are younger [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have read the recent cross-sectional study by Webber et al 1 with great interest, which examined the factors that impacted the frequency of social participation and community ambulation among patients with osteoarthritis (OA). The statistical power and the degree of reliability were ensured by the utilization of a populationbased database.…”
Section: Social Activity Physical Exercise and Health-related Quality...mentioning
confidence: 99%